THE HEMOGLOBIN, RDW, AND MEAN CORPUSCULAR VALUES IN PATIENTS WITH BETA-THALASSEMIA/HEMOGLOBIN E DISEASE AND BETA-THALASSEMIA TRAIT - Vinisia Setiadji; Bidasari Lubis; Adi Koesoema Aman; Herman Hariman (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Beta-thalassemia/hemoglobin E disease is a condition where there is double heterozygosity of beta-thalassemia trait and hemoglobin E trait. This produces a condition with more severe phenotypic appearance compared to beta thalassemia trait and hemoglobin E trait. Logically the Mean Corpuscular Values (MCV) of beta-thalassemia/hemoglobin E disease should also be worsened. The aim of this study was to assess the hemoglobin level, RDW, and MCV between beta-thalassemia/hemoglobin E disease and beta thalassemia trait. The researchers hereby studied eleven cases from two families who were detected to have beta-thalassemia/hemoglobin E disease. Family-1 with beta-thalassemia trait had MCV 68 fL and 65 fL, the MCH value was 21 pg and 20 pg, respectively. In Family-2, mother with beta-thalassemia trait, had MCV 60.2 fL and MCH 18. 8 pg. Daughters with beta-thalassemia/hemoglobin E disease from subjects 1 and 2 whose blood were taken repetitively during visits to the hematology clinic, had mean±SD of MCV 70.8±4.9 fL and Mean Corpuscular Hemoglobin (MCH) value 22.8±2.3 pg. They were significantly higher than the ones with beta-thalassemia trait (p<0.05). Moreover, there were found that the MCV from post-transfusion state were significantly higher than the pre-transfusion state (p<0.001). Based on the study, it could concluded that the MCV from subjects with beta-thalassemia/hemoglobin E disease were persistently higher than the beta-thalassemia trait. The role of blood transfusion in patients with beta-thalassemia/hemoglobin E disease seems to play a part in the result of a discrepancy in this matter.